Global Inequality and American Foreign Policy in the 1970s - Franczak, Michael, 1990- (Book collections on Project MUSE., 2022)
"This book explores the US foreign policy response to G-77's New International Economic Order through the administrations of Richard Nixon, Gerald Ford, Jimmy Carter, and Ronald Reagan"--